Municipal forest management in Latin America - Ferroukhi, Lyès (International Development Research Centre, 2004)
The book was written for three different purposes: (i) better understand the types of powers assigned to municipalities to this day, (ii) better understand the increasingly important role played by municipalities in forest management, (iii) analyze the opportunities that were created and the challenges faced by the decentralization processes in the region. The book compiles findings from in-depth studies conducted in 6 countries: Bolivia, Brazil, Costa Rica, Nicaragua, Honduras and Guatemala.